PERANCANGAN APLIKASI E-RAPOR MATA PELAJARAN AL-QUR'AN PADA SEKOLAH MENENGAH PERTAMA ISLAM TERPADU SAMAWA CENDEKIA (SMP IT SAMAWA CENDEKIA) DENGAN METODE WATERFALL BERBASIS WEBVIEW PADA PLATFORM ANDROID - Yudi Mulyanto; Natasya Awra Fadilah (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
The application is designed to facilitate the teaching and learning of Al-Qur'an by providing an intuitive and informative interface for teachers, parents, and students. The software development method used in creating this application is the waterfall method due to its sequential and structured approach, suitable for projects with clear specific needs and ensuring systematic management from planning to implementation. The result of this research is an application that presents structured student report information, including academic grades, progress evaluations, and recommendations for further development. The application also utilizes WebView technology to dynamically present Al-Qur'an content and facilitate efficient use across various Android devices.